Principles of lasers and optics - Chang, William S. C. 1931-2015 (Cambridge University Press, 2005)
This book describes both the fundamental principles of the laser and the propagation and application of laser radiation in bulk and guided-wave components. All solid state, gas, and semiconductor lasers are analyzed in a uniform manner as macroscopic devices with susceptibility originating from quantum mechanical interactions.